2012
DOI: 10.1098/rsif.2012.0471
|View full text |Cite
|
Sign up to set email alerts
|

Variation in carotenoid–protein interaction in bird feathers produces novel plumage coloration

Abstract: Light absorption by carotenoids is known to vary substantially with the shape or conformation of the pigment molecule induced by the molecular environment, but the role of interactions between carotenoid pigments and the proteins to which they are bound, and the resulting impact on organismal coloration, remain unclear. Here, we present a spectroscopic investigation of feathers from the brilliant red scarlet ibis (Eudocimus ruber, Threskiornithidae), the orangered summer tanager (Piranga rubra, Cardinalidae) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…Birds must produce plumage coloration using only those carotenoid compounds that are found in the diet, either directly or as precursors. If these dietary carotenoids are metabolically modified, only a limited number of modifications is possible that change carotenoid absorptive properties (Britton ; but see Mendes‐Pinto et al ). Thus carotenoid hue might be thought of as a bounded, discrete character that can easily be switched back and forth between yellow and red with the gain or loss of particular enzymes or their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Birds must produce plumage coloration using only those carotenoid compounds that are found in the diet, either directly or as precursors. If these dietary carotenoids are metabolically modified, only a limited number of modifications is possible that change carotenoid absorptive properties (Britton ; but see Mendes‐Pinto et al ). Thus carotenoid hue might be thought of as a bounded, discrete character that can easily be switched back and forth between yellow and red with the gain or loss of particular enzymes or their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Even among carotenoidpigmented birds, however, the identity and metabolic modification of particular plumage colorants only tell part of the story. For example, the same pigment (canthaxanthin) can produce red, redorange, and even purple plumage in different species, depending on molecular alignment and interaction with proteins (Mendes-Pinto et al 2012). Similarly, two species in the present study (Serinus pusillus and Carduelis carduelis) rely exclusively on modified yellow pigments to produce red plumage, demonstrating a rare evolutionary pathway to achieve red feathers within this taxon (though this phenomenon has previously been described for red-shouldered widowbirds Euplectes axillaris; Andersson et al 2007).…”
Section: Dietary Yellowmentioning
confidence: 99%
“…Raman and mid-infrared spectroscopies are versatile methods for analysing chemical composition and molecular structure. Notably, Veronelli et al [35] determined chemical characteristics of psittacofulvins from a Raman spectroscopic study comparing parrot feather pigments and carotenoids, and Mendes-Pinto recently used Raman spectral information to link feather coloration with carotenoid-contortion [36]. Previous studies of spheniscin pigments have identified chromatic, chromatographic retention-time and solubility properties [17].…”
Section: Introductionmentioning
confidence: 99%